1996
DOI: 10.1073/pnas.93.8.3710
|View full text |Cite
|
Sign up to set email alerts
|

The use of spreading depression waves for acute and long-term monitoring of the penumbra zone of focal ischemic damage in rats.

Abstract: Slow potential recording was used for longterm monitoring of the penumbra zone surrounding an ischemic region produced by middle cerebral artery (MCA) occlusion in adult hooded rats (n = 32). Four capillary electrodes were chronically implanted at 2-mm intervals from AP -3, L 2 (El) to AP 0, L 5 (E4). Spontaneous or evoked slow potential waves of spreading depression (SD) were recorded during and 4 h after a 1-h MCA occlusion and at 2-to 3-day intervals afterward for 3 weeks. Duration of the initial focal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In particular, the propagation of the AD to the hypoxic/hypoglycemic region (penumbral area) surrounding the ischaemic core may extend the damage. Consistently, it has been demonstrated that one major factor contributing to neuronal death in the penumbra is the propagation of spreading depression waves ( Koroleva & Bures, 1996 ). Because the penumbra constitutes potentially salvageable tissue, the molecular responses of the perifocal neurons to focal ischaemia and AD are of interest ( Obeidat et al ., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the propagation of the AD to the hypoxic/hypoglycemic region (penumbral area) surrounding the ischaemic core may extend the damage. Consistently, it has been demonstrated that one major factor contributing to neuronal death in the penumbra is the propagation of spreading depression waves ( Koroleva & Bures, 1996 ). Because the penumbra constitutes potentially salvageable tissue, the molecular responses of the perifocal neurons to focal ischaemia and AD are of interest ( Obeidat et al ., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NMDA antagonists can reduce the size of the penumbra in models of both ischaemia [ 45] and traumatic brain injury [ 37]. Therefore, c‐fos expression may be a marker for the perilesional depolarization or spreading depression observed in the penumbra of ischaemic lesions, which is thought to enhance cell death by energy depletion [ 30, 35, 60]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SD recovery in isolated retinal preparation is independent of O 2 availability, albeit with substantially elevated glucose levels (501). Moreover, pharmacological interventions that diminish the hyperemic response to SD also prolong the DC shift (155,353), and the durations of peri-infarct SDs are prolonged in hypoperfused penumbra despite relatively mild ischemia (202,229). These data suggest that tissue perfusion per se may be critical for the restoration of ionic homeostasis.…”
Section: Role Of Vasculature In Spreading Depression Recoverymentioning
confidence: 96%